G265(P) Gastroenteritis aggressive versus slow treatment for rehydration (gastro study): a descriptive analysis. (12th March 2018) - Houston, K; Gibb, J; Mpoya, A; Obonyo, N; Olupot-Olupot, P; George, E; Gibb, D; Maitland, K
Abstract : Aims: The World Health Organisation (WHO) rehydration guidelines (Plan C) for children with acute gastroenteritis (AGE) and severe dehydration are widely practiced in resource-poor settings, yet have never been evaluated in a clinical trial. GASTRO study will compare the safety and efficacy of two rehydration regimens: standard rapid rehydration (Plan C) versus a slower regimen and inform definitions for outcomes of a larger phase III trial. Methods: GASTRO is a multi-centre, open Phase II randomised controlled trial of 120 children aged 2 months to 12 years admitted with severe dehydration secondary to AGE. Children with severe malnutrition, chronic diarrhoea and known congenital/rheumatic heart disease are excluded. Children are enrolled in 3 centres in East Africa and randomised 1:1 to standard rapid rehydration (WHO plan 'C' – 100 mls/kg over 3–6 hours according to age, plus additional boluses for children presenting in shock) or to a slower rehydration regimen (100 mls/kg given over 8 hours and without additional boluses). Primary outcome is frequency of adverse events. Secondary outcomes focus on measures related to assessment of severity of dehydration, and response to treatment. Results: Enrolment is ongoing. By 21 st September 2017 61 children had been enrolled. Baseline characteristics across the two groups are consistent: median age 9 months (IQR 7–14), 67% males, median duration of diarrhoea and vomiting is 3 days, the majority are lethargic, thirsty and irritable on admission (70%) and main features of dehydration are sunken eyes (100%), prolonged skin pinch (64%), reduced/absent tears (100%), dry/sticky mucous membranes (98%). Features of shock (cool peripheries, weak and fast pulse, and prolonged capillary refill) exist in 33% of the patients at admission, and no child had severe hypotension. Median weight loss is 5.7%. We have not completed recruitment and therefore cannot present outcomes at this stage. Discussion: There have been two main challenges when operationalising this trial. Firstly staff training and confidence with ensuring accurate fluid balance documentation. Secondly there has been slow recruitment as a result of national medical strikes and a severe drought across East Africa resulting in higher numbers of children fulfilling severe malnutrition anthropometric criteria and therefore being excluded.